PENGELOLAAN PENERIMAAN PAJAK KENDARAAN BERMOTOR (PKB) PADA DINAS PENDAPATAN DAERAH PROVINSI RIAU TAHUN 2010-2014 - Raja Kharisma Putri Pertiwi; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Revenue Department tasked with carrying out the affairs of local government based on the principle of regional autonomy and the establishment of a task and assign areas of revenue to implement them. Organizing authority in bestowed by the government to the Governor as representative of the Government in the framework of deconcentration. The problem is still a lack of human resources, infrastructure, awareness of the taxpayer, as well as the supervision of officers associated with the management of motor vehicle taxes in 2010-2014.Objective: 1) To determine the management of motor vehicle tax receipts that occurred in Riau Province Regional Revenue Office 2010-2014 2) To determine the obstacles that occur in vehicle tax collections Department of Revenue Riau Province in 2010-2014 3) To know the effort which is to overcome the obstacles that occur in motor vehicle tax collections in the Department of Revenue Riau Province 2010-2014. The informants were taken from some employees Department of Revenue Riau Province. Population serve as informants for this study using qualitative research. The types and sources of data used primary data, ie data obtained directly from the respondents and secondary data, ie data obtained through reporting, books and records. Data collection technique used interview, observation, documentation. Data analysis techniques by means of data collection, data reduction, data presentation, and draw conclusions.Based on the results of research known motor vehicle tax revenue management in the Department of Revenue Riau Province in 2010-2014 was done by planning (perencaanan), organizing (organizing), motivating (motivation), controlling (supervision), evaluating (evaluation). Barriers motor vehicle tax revenue management in the Department of Revenue Riau Province in 2010-2014 was the lack of information, lack of awareness of the taxpayer to pay taxes. Calo located in each UPT, motor vehicle theft and the withdrawal of motor vehicles by the dealer so that taxpayers are reluctant to pay taxes. Efforts in encountering impediments to improvement of information, monitoring each Unit to reduce brokers.Keywords:Management,Tax and Motor Vehicle